Lexton MacCarthy Residence (Oz, 2003)
Isolating the hillside house as a building type is very important for architectural discourse. Sloping sites offered California modernists, Wright, Schindler, Neutra, Lautner, and others, the opportunity to invent new forms, transforming the house. Continuing in this tradition the Lexton/MacCarthy site offered wonderful west facing views of Los Angeles and suggested a formal strategy of an abstract geometrical form conceived as a play of positive and negative volumes.